2014
DOI: 10.1007/s11746-014-2416-3
|View full text |Cite|
|
Sign up to set email alerts
|

Retardation of Crystallization of Diacylglycerol Oils Using Polyglycerol Fatty Acid Esters

Abstract: Liquid oil containing high concentrations of diacylglycerols (DAG > 80 %, hereafter referred to as DAG‐rich oil) is generally more likely to cause precipitation at chilled temperatures (clouding phenomena) than triacylglycerol‐based oil. The clouding phenomena that occur during long‐term storage of DAG‐rich oil are unwanted in consumer products and therefore, must be prevented. In the present study, we attempted to retard precipitation by adding food emulsifiers, polyglycerol fatty acid esters (PGFE) contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…of L195, the crystallisation of PO did not take place. The nucleation retardation may be related to molecular interactions between fat and additives, which occur during the cluster formation process so that the cluster formation is prohibited (Saitou et al, 2014). According to the similarity/dissimilarity concept, during the crystal growth, the incorporation of crystallising materials at the kink sites on the growth steps could be obstructed by the additives (Shimamura et al, 2013).…”
mentioning
confidence: 99%
“…of L195, the crystallisation of PO did not take place. The nucleation retardation may be related to molecular interactions between fat and additives, which occur during the cluster formation process so that the cluster formation is prohibited (Saitou et al, 2014). According to the similarity/dissimilarity concept, during the crystal growth, the incorporation of crystallising materials at the kink sites on the growth steps could be obstructed by the additives (Shimamura et al, 2013).…”
mentioning
confidence: 99%
“…The crystallization behavior of SLs may also be altered by adding minor components. For instance, in DAG‐rich oils (DAG > 80%) unpleasant “clouding” phenomenon usually occurs during storage as a result of crystallization of high‐melting DAG fractions (Saitou, Homma, Kudo, Katsuragi, & Sato, ). This problem has been solved through the addition of polyglycerol fatty acid esters (PGFEs), mainly due to formation of a liquid‐crystal‐like supramolecular complex structure containing the high‐melting DAG fractions and PGFEs (Saitou et al., ; Saitou et al., ).…”
Section: Physicochemical Properties Of Slsmentioning
confidence: 99%
“…For instance, in DAG‐rich oils (DAG > 80%) unpleasant “clouding” phenomenon usually occurs during storage as a result of crystallization of high‐melting DAG fractions (Saitou, Homma, Kudo, Katsuragi, & Sato, ). This problem has been solved through the addition of polyglycerol fatty acid esters (PGFEs), mainly due to formation of a liquid‐crystal‐like supramolecular complex structure containing the high‐melting DAG fractions and PGFEs (Saitou et al., ; Saitou et al., ). Other minor components such as phytosterol esters (Daels, Foubert, & Goderis, ), sucrose behenate (Domingues, Da Silva, Ribeiro, Chiu, & Gonçalves, ), lecithin (Rigolle et al., ), and sugar (West & Rousseau, ) have also been reported to adjust the crystallization and melting behavior of fats and oils.…”
Section: Physicochemical Properties Of Slsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that when an emulsifier is used above its equilibrium solubility concentration, it crystallizes ahead of the bulk fat and promote crystallization by serving as a template while at low concentrations, the emulsifier causes de-clustering in the molecular packing of TAGs (i.e. mismatched assembling properties due to differences in structural features) resulting in retardation of crystallization [15,20,21]. Recent studies also revealed that the long chain saturated MAGs had a distinct effect on milk fat crystallization by inducing heterogeneous nucleation resulting in earlier crystallization, whereas no such effect was observed for mid chain saturated and unsaturated MAGs even when used at concentration that was seven fold higher than long chain saturated MAGs [22].…”
Section: Influence Of Minor Lipid Components On Fat Crystallizationmentioning
confidence: 99%